Cognitive training for children with ADHD: a randomized controlled trial of cogmed working memory training and ‘paying attention in class’ - van der Donk, Marthe; Hiemstra-Beernink, Anne-Claire; Tjeenk-Kalff, Ariane; van der Leij, Aryan; Lindauer, Ramón (Frontiers in Psychology, 2015)
The goal of this randomized controlled trial was to replicate and extend previous studies of Cogmed Working Memory Training (CWMT) in children with ADHD. While a large proportion of children with ADHD suffer from academic difficulties, only few previous efficacy studies have taken into account long term academic outcome measures. So far, results regarding academic outcome measures have been inconsistent. Hundred and two children with ADHD between the age of 8 and 12 years (both medicated and medication naïve) participated in current randomized controlled trial. Children were randomly assigned to CWMT or a new active combined working memory- and executive function compensatory training called ‘Paying Attention in Class’. Primary outcome measures were neurocognitive functioning and academic performance. Secondary outcome measures contained ratings of behavior in class, behavior problems and quality of life. Assessment took place before, directly after and six months after treatment. Results showed only one replicated treatment effect on visual spatial working memory in favor of CWMT. Effects of time were found for broad neurocognitive measures, supported by parent and teacher ratings. However, no treatment or time effects were found for the measures of academic performance, behavior in class or quality of life. We suggest that methodological and non specific treatment factors should be taken into account when interpreting current findings. Future trials with well-blinded measures and a third ‘no treatment’ control group are needed before cognitive training can be supported as an evidence-based treatment of ADHD. Future research should put more effort into investigating why, how and for whom cognitive training is effective as this would also potentially lead to improved intervention- and study designs.